Pore-scale modelling of electrochemically reactive flow - Lavrentev, Artem (My University, 2022)
Electrochemistry, a field revolving around charge transport, is omnipresent in our every-day life. It is found in batteries, water treatment, medicine, and food processing, to name a few. Water dissolves more substances than any other liquid and is consequently easily polluted. Self-evidently, drinking water quality is crucial to our health. Water disinfection refers to any process that removes pathogens from drinking water. Electrochemical treatments are one of the processes used for water disinfection and are advantageous wherewith required chemicals are formed in situ, while needing less and in some cases no other additional chemicals. Porous electrodes are becoming increasingly prevalent in electrochemical systems due to enhanced features such as reaction kinetics and mass transport. The arising complexity of the electrochemical processes at the pore-scale, involving multicomponent reactive flow, poses numerous challenges to the currently available experimental methods and the macro-continuum mathematical models. This work is aimed at the development of pore-scale numerical model using the Lattice Boltzmann Method and focuses on anodic oxidation under the aqueous condition. Historically, iodine has been used as a disinfectant for wounds as well as water. Excess consumption however can have adverse health effects such as thyroid disease. Using potassium iodide for water disinfection allows for iodine to be produced via anodic oxidation and then consumed through cathodic reduction. The relationship between concentrations, flow rates and potentials are investigated in a flow-through porous electrode. [...]
Keywords: Electrochemistry; Lattice Boltzmann Method